Bisphosphonates and their clinical implications in endodontic therapy. (9th November 2012) - Moinzadeh, A.‐T.; Shemesh, H.; Neirynck, N. A. M.; Aubert, C.; Wesselink, P. R.
Abstract This review gives an overview of the factors that may play a role in the development of osteonecrosis of the jaw in patients treated with bisphosphonates (BPs) and undergoing nonsurgical endodontic treatment as well as some recommendations for its prevention. BPs are a widely prescribed group of drugs for diverse bone diseases. The occasional but devastating adverse effect of these drugs has been described as bisphosphonate‐related osteonecrosis of the jaw (BRONJ). As this condition is debilitating and difficult to treat, all efforts should be made to prevent its occurence in patients at risk. The main triggering event is considered to be dental extraction. Even though nonsurgical endodontic treatment appears to be a relatively safe procedure, care remains essential. After an overview of this class of drugs, the clinical presentation, epidemiology and pathogenesis of BRONJ, as well as the possible risk factors associated with its development after nonsurgical endodontic treatment will be described. Finally, several strategies will be proposed for the prevention of BRONJ during nonsurgical endodontic treatment.